Evaluation System at School Level in Nepal: Major Pitfalls and Considerations - Gyawali, Yadu Prasad (Marsyangdi Journal, 2021)
This paper aims to explore the pitfalls of the current evaluation system at the school level in Nepal focusing on the major consequences of educational practices as the output of the evaluation system. Although the provisions of formative assessment tools such as portfolio management and project work were included in the curriculum framework and policy documents, the evaluation process was based on a theoretical basis. Similarly, the judgmental written examination for assessing theoretical aspects and Continuous Assessment System (CAS) with backward-looking nature were involved in the evaluation process. The paper suggests to the educational stakeholders for the practical application and evaluation of soft-skills associated methods such as communication, creativity, cooperation and collaboration of basic and secondary students to promote formative evaluation and the curriculum concept of ’assessment for learning in Nepal.